2020
DOI: 10.1007/s12070-020-02239-4
|View full text |Cite
|
Sign up to set email alerts
|

An Epidemiological Study of Cut Throat Injury During COVID-19 Pandemic in a Tertiary Care Centre

Abstract: To find out incidence, prevalence, various modes and pattern of cutthroat injury during COVID-19 pandemic and compare with prior non pandemic period. To find out the various factor influencing the suicidal cutthroat and establish the temporal association of suicidal cutthroat with COVID-19 pandemic. It is a retrospective study of cutthroat patients who were managed in ENT Dept. VIMSAR, Burla, Sambalur, Odisha, India from 1st September 2019 to 31st August 2020. Source of information are casualty, IPD and OT reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…One small study (n = 14) in Rishikesh, India reported an increase in suicide-related psychiatric emergencies in the 4 weeks after lockdown compared with the preceding 4 weeks (11 vs 3-Fig 3) [33]. Another small hospital study (n = 13) from the district of Burla, in the Indian city of Sambalpur, reported the number of suicidal cut-throat injuries increased from 4 in the 6 months prior to the pandemic to 9 in the following 6 months (Fig 3) [31].…”
Section: Plos Global Public Healthmentioning
confidence: 97%
See 1 more Smart Citation
“…One small study (n = 14) in Rishikesh, India reported an increase in suicide-related psychiatric emergencies in the 4 weeks after lockdown compared with the preceding 4 weeks (11 vs 3-Fig 3) [33]. Another small hospital study (n = 13) from the district of Burla, in the Indian city of Sambalpur, reported the number of suicidal cut-throat injuries increased from 4 in the 6 months prior to the pandemic to 9 in the following 6 months (Fig 3) [31].…”
Section: Plos Global Public Healthmentioning
confidence: 97%
“…India (n = 5), Sri Lanka (n = 1) and Nepal (n = 2) represented the South Asian region with 8 studies [12,[31][32][33][34][35][36][37], with only one (from Sri Lanka) rated as being of reasonable quality.…”
Section: South Asiamentioning
confidence: 99%
“…One small study (n=14) in Rishikesh, India reported an increase in suicide-related psychiatric emergencies in the 4 weeks after lockdown compared with the preceding 4 weeks (11 vs 3 - Figure 3) (33). Another small hospital study (n=13) from the district of Burla, in the Indian city of Sambalpur, reported the number of suicidal cut-throat injuries increased from 4 in the 6 months prior to the pandemic to 9 in the following 6 months (Figure 3) (31).…”
Section: Resultsmentioning
confidence: 99%
“…India (n=5), Sri Lanka (n=1) and Nepal (n=2) represented the South Asian region with 8 studies (12,(31)(32)(33)(34)(35)(36)(37), with only one (from Sri Lanka) rated as being of reasonable quality.…”
Section: South Asiamentioning
confidence: 99%
“…With regards to suicide attempts treated in hospitals, the Psychiatric Liaison service experienced an increase in consultations for suicide attempts (OR 8.0, 95% CI 2.03 to 31.57, p = 0.003), where the most common causes were related to relationship problems and loss of privacy during the lockdown [78]. In the surgical services, both in India and Scotland, the number of cases of suicide attempts by stabbing increased [79,80].…”
Section: Incidence Of Suicide Attemptsmentioning
confidence: 99%